Emotions, attitudes, and appraisal in the management of climate-related risks by fish farmers in Northern Thailand - Louis Lebel (2018)
© 2016, © 2016 Informa UK Limited, trading as Taylor & Francis Group. Many previous studies have documented that farmers are risk-averse, while other studies have shown that farmers analyze and estimate risks. Conventional risk aversion measures and analytical judgment often do not fully explain decision behavior. Thus, it may be necessary to consider emotions. The objective of this study was to enhance understanding of the interactions between attitudes, analysis, and emotions in making risk decisions. The study used a mixture of methods, including: a tablet game, risk aversion scales, in-depth interviews, and focus group discussions with fish cage farmers in Northern Thailand. There was no significant difference in risk aversion with respect to gender, age group, or region. Having sufficient capital made it possible to take more risks. Recently being impacted by floods or droughts, or being very concerned with climate change, was not associated with taking fewer risks. Measures of risk aversion did not predict risk decisions. Feeling worried, concerned, anxious, or stressed were the most common negative emotions referred to in interviews. Fear was a reason for not taking risks. Common positive emotions were joy, excitement, and feeling relaxed or relieved. Men who expressed feeling excited or thrilled chose riskier, higher stocking densities in games than women. A common belief was that men were quicker and more confident when making decisions. Another was that emotions had little impact on decisions, but were a response to success and failure–a claim inconsistent with other findings that imply emotions are also important prior to stocking decisions, and while waiting for the harvest. Fear and anxiety in the period prior to harvest may help motivate risk management practices, such as close monitoring and aeration. In conclusion, emotions may play a more important role in making decisions about climate-related risks than was previously recognized.